Measuring the Effects of HRM Functions «Reward, Benefit, and Recognition» and «Performance Management» on Innovation and Entrepreneurship: A Practical Study in Pharmaceutical Organizations - Naser, Mohamed (The Arab Journal of Administration, 2020)
Purpose- Human Resource Management (HRM) in any organization was and still crucial for innovation and entrepreneurship. An empirical study was examined to scrutinize the effect of some (HRM) functions (polices) on innovation and entrepreneurship to achieve goals of business. Design / Approach- This article primarily includes two parts. In first part, author reviews the concept of: (HRM) functions, innovation and entrepreneurship in the existing literature. In second part, a questionnaire was conducted on the selected participants. The data were analyzed using demographic, correlation, and regression statistics. Findings- The results show that the mentioned functions of (HRM) are significantly related to perceived innovations over time. Rewards, benefits, and recognition have statistically a moderate effect on perceived innovations then entrepreneurship. While performance management has statistically a good effect on perceived innovations then entrepreneurship Originality / Value- The basic objective is to measure precisely the effect of each function of (HRM) on innovation and entrepreneurship. A research model was developed and tested. Besides, the role of endogenous forces including change acceptance culture and the power of link between perceived innovations were also considered as important elements in designing the relationships. The practical contribution of this article is that the results would help to choose the best mix and investment between (HRM) functions, which would significantly contribute to the success of innovation and entrepreneurship. Specifically, the understandings of whether those current (HRM) functions in this sector are more or equal or less innovative than other functions to identify the appropriate skills, resources, and plans.